Patients’ preferences for genomic diagnostic testing in chronic lymphocytic leukaemia: a discrete choice experiment - Buchanan, J; Wordsworth, S; Schuh, A (Springer (Adis), 2016)
Background: Genomic information could help to reduce the morbidity effects of inappropriate treatment decisions in many disease areas, in particular cancer. However, evidence of the benefits that patients derive from genomic testing is limited. This study evaluated patient preferences for genomic testing in the context of chronic lymphocytic leukaemia (CLL). Methods: We used a discrete choice experiment (DCE) survey to assess the preferences of CLL patients in the United Kingdom for genomic testing. The survey presented patients with 16 questions in which they had to choose between two possible test scenarios. Tests in these scenarios were specified in terms of six attributes, including test effectiveness, test reliability and time to receive results. Results: 219 patients completed the survey (response rate 20%). Both clinical and process-related attributes were valued by respondents. Patients were willing to pay £24 for a 1% increase in chemotherapy non-responders identified, and £27 to reduce time to receive test results by one day. Patients were also willing to wait an extra 29 days for test results if an additional one-third of chemotherapy non-responders could be identified, and would tolerate a genomic test being wrong 8% of the time to receive this information. Conclusion: CLL patients value the information that could be provided by genomic tests, and prefer combinations of test characteristics that more closely reflect future genomic testing practice than current genetic testing practice. Commissioners will need to carefully consider how genomic testing is operationalised in this context if the benefits of testing are to be realised.